Biopetrol synthesized from rubber seed oil through heterogeneous catalytic cracking using zeolites catalyst: effect of acetone in solvent extraction of rubber seed - Thanimalay, Dinesh Raj (2012)
Today scenario imposes great importance on the alternative of fossil fuel.In line with that is the development of biofuel derived from biomass.Common feedstocks for such process nowadays are corn,soya oil,palm oil etc.However, the rubber seed oil(RSO)can be extracted from its kernel to be derived as biopetrol.This method is much favarouble as the high concentration of fatty acids in rubber seeds.Also, rubber seeds are abundant and easily available throughout Malaysia.It will also be a secondary income for rubber plantation workers via collecting rubber seeds and selling it.The objectives of this experiment are;to synthesize isooctane form rubber seed oil using Zeolite as catalyst,to study the effect of solvent(Acetone)in the extraction of fatty acids from rubber seeds,and to analyze isooctane concentration through gas chromatography.Rubber seeds’ kernel are cleaned,shelled,ground,blended,and dried. Extraction of fatty acids from rubber seeds are done by Soxhlet extraction method using Acetone as extraction solvent.The efficiency of solvent is analyzed by using different mass ratio between the solvents and rubber seeds kernel starting from 1:2 to 1:5.Rotary evaporator was used to evaporate the solvent, leaving behind crude rubber seed oil.The catalytic cracking of the mixture of 25ml of RSO and 5g of Zeolite catalyst at 3500C for 45 minutes is to boost up the rate of reaction of breaking the long chains of fatty acids.The final product is analyzed through Gas Chromatography.Then the results of chromatograms are compared with the standard isooctane calibration curve. Through the calibration curve using backward calculation, the yield of biopetrol is determined.From this experiment the actual Isooctane concentration is about 53% to 78%.The result shows higher than expected result because of the factor of random reaction in catalytic cracking,hydrocarbon isomerization,high quantity of fatty acids in rubber seed oil which have been converted to Isooctane,and the small volume of sample analysis.This research can be further improved by the use of Supercritical CO2 in extraction process, filling of inert gases or nitrogen in catalytic cracking chamber,elimination of impurities and minimization of human errors.